Male and female genital lichen sclerosus. Clinical and functional classification criteria - Latini, Alessandra; Cota, Carlo; Orsini, Diego; Cristaudo, Antonio; Tedesco, Marinella (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Lichen sclerosus (LS) is a chronic inflammatory disease affecting mainly the genital mucous membranes in both sexes. In the past, different terms were used to describe the disease, rendering a unique and specific clinical classification impossible. New therapeutic approaches are being defined, which may contribute to a proper clinical management, however, stage classification is essential to better define appropriate treatment for every stage of the disease. One hundred and fifteen patients (50 women and 65 men) with a diagnosis of LS were enrolled between January 2014 and September 2016. All patients underwent cutaneous biopsy to confirm the clinical diagnosis of LS. Clinical and symptomatological parameters were used in order to put the patients into the correct stage of LS. The Dermatology Life Quality Index (DLQI) was used to classify patients based on subjective symptoms. Different cutaneous alterations and structural modifications of the genital mucosa were also taken into consideration in order to assign every patient to a specific stage. Lichen sclerosus is clinically described differently in females and in males and every form of LS is placed in one of two stages according to the degree of severity: early and late stages. Within the clinical practice, it is useful to screen patients for groups of early or later forms of the disease in order to obtain a uniform subdivision of patients; those who may benefit from localized treatments, require a systemic drug and must undergo physical treatments (surgical, stem cells infiltrations).